Postmaterialism and the Australian Party System - Charnock, David; Ellis, Peter (The Australasian Political Studies Association, 2002)
In this paper we explore the positioning of Australian political parties at the 2001 federal election using data from the Australian Election Study and discuss some of the strategic implications. We focus on some of the attitudes of Senate voters for the various parties, concentrating on how Inglehart's postmaterialism measures can be used to supplement more traditional left-right descriptions of the party system. In order to make some assessment of the significance of the electoral context we make some comparisons with the 1998 election and also examine party positioning in relation to other sets of attitudes about potentially salient issues.